Implementasi PSAP No.05 Atas Akuntansi Persediaan Pada Dinas Perindustrian dan Perdagangan DIY - Florentina Cindy Finishtya; Triya Nur Safitri (Jurnal Akuntansi dan Pajak, 2023)
The purpose of this study is to analyze the inventory treatment at the Department of Industry and Trade of DIY based on the provisions of PSAP No. 05 by using data analysis methods in the form of interviews, observations and documentation carried out directly at the Department with the purpose of producing more precise reports in analyzing the phenomena that the researchers studied. The researcher found that the inventory accounting treatment at the DIY Industry and Trade Office on the indicators of inventory overview, inventory recognition, and inventory measurement applied was appropriate based on PSAP No. 05, but based on indicators of inventory disclosure it is still not in accordance with PSAP No. 05. This is because the financial report of the Department of Industry and Trade of DIY does not include the inventory valuation method in the Notes to Financial Statements. This valuation method is not included because the financial format used so far does not report the inventory valuation method, but PSAP No. 05 asked to report the inventory valuation method policy. Based on the results of the interview, information was obtained that the financial report format used by the department is the format of the Audit Board of the Republic of Indonesia so that the department uses the financial report format.